Pion-kaon femtoscopy as a probe of the space-time emission anisotropies due to interactions at the hadronic stage of matter evolution in relativistic heavy-ion collisions - Chakraborty, Purnendu; Kornakov, Georgy; Kisiel, Adam; Sinyukov, Yuriy; Shapoval, Volodymyr; Dash, Sadhana (Physical Review C, 2026)
Emission asymmetries between pions and kaons reflect the role of the hadronic phase in the cooling of a droplet of deconfined strongly interacting matter. This study compares results from two models at the same collision energy of √s_NN = 5.02 TeV to investigate how interactions in the hadronic phase affect particle emission. The first model, the integrated hydrokinetic model (iHKM), provides a complete description of all stages of the evolution; from the initial scattering and thermalization to the final hadronic state, while the second model, LQTH (LHYQUID + THERMINATOR 2), assumes a sudden conversion into hadrons, neglecting further interactions. To increase the sensitivity to hadronic interactions, the analysis was performed as a function of the pair transverse velocity for pairs with nearly equal velocity vectors. The obtained predictions are compared with previously measured ALICE data at √s_NN = 2.76 TeV as a function of the cube root of the average particle multiplicity density at midrapidity, showing that both radii and emission asymmetries scale with particle multiplicity, regardless of the collision energy. The iHKM reproduces the measured trends both qualitatively and quantitatively, whereas the LQTH model requires additional parameters—in particular, a time delay in the emission of kaons—to achieve quantitative agreement. The comparative analysis also indicates a possible nonmonotonic behavior of the asymmetry as a function of transverse velocity, and a constant scaling of the ratio between the emission asymmetry and femtoscopic radii with particle multiplicity. These results highlight the importance of including interactions in the hadronic stage for a complete description of the emission function.